Pengaruh Lama Penyimpanan Telur terhadap Transovarial Infection Rate Virus DEN-3 pada Nyamuk Aedes aegypti - Tri Wahono; Sitti Rahmah Umniyati; Tri Baskoro Tunggul Satoto (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2019)
Transovarial transmission of dengue virus is important phenomenon causes dengue virus survival during inter-epidemic period. The purpose of this study was to analyze effect of egg storage duration on DEN-3 virus Transovarial Infection Rate (TIR) in Aedes aegypti mosquitoes. This was laboratory research with experimental design. Ae. aegypti was infected with the DEN-3 virus per-orally and allowed to undergo its gonotrophic cycle. Eggs stored at room temperature (25±3oC) and relative humidity (70±5%) for 0, 1, 2 and 3 months. Hatched eggs then colonized until become adult mosquito. Sample was taken from colonies at 4, 8, 16 days old. Headsquash of mosquitoes was preparedwith Streptavidin Biotin Peroxidase Complex (SBPC) immunocytochemical method using DSSE 10 monoclonal antibody and detected the presence virus antigen. Transovarial infection rate was determined by counting percentage of positive samples. Data were analyzed by linear regression test. Result of this study showed that in 4, 8, 16 samples showed lowest TIR on 0 month storage (33,33%, 33,33%; 40,00%) and highest TIR observed on 2 month storage (76,67%; 66,67%, 76,67%). Statistical test showed significantly different result (p = 0,013) with α = 0,05 and R2 = 0,476. The duration of egg storage effect on DEN-3 virus TIR in Ae. aegypti mosquito with 47.6% contribution.